2018
DOI: 10.3390/s18103382
|View full text |Cite
|
Sign up to set email alerts
|

A High-Performance Optoelectronic Sensor Device for Nitrate Nitrogen in Recirculating Aquaculture Systems

Abstract: The determination of nitrate nitrogen (NO3-N) in recirculating aquaculture systems is of great significance for the health assessment of the living environment of aquatic animals. Unfortunately, the commonly used spectrophotometric methods often yield unstable results, especially when the ambient temperature varies greatly in the field measurement. Here, we have developed a novel handheld absorbance measurement sensor based on the thymol-NO3-N chromogenic rearrangement reaction. In terms of hardware, the senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The concentration of nitrate and nitrite in water has become one of the indexes for evaluating water quality. Therefore, the detection of nitrate and nitrite in water samples at low concentrations has been the focus of research [11].So far, many methods have been used to detect nitrate and nitrite, such as spectrophotometry [12][13][14], chemiluminescence [15,16], chromatography [17], fluorescence [18,19] and electrochemical methods [20][21][22]. Among them, the electrochemical method is one of the most commonly used detection methods because of its advantages of being low cost, fast, direct and high efficiency [23].…”
mentioning
confidence: 99%
“…The concentration of nitrate and nitrite in water has become one of the indexes for evaluating water quality. Therefore, the detection of nitrate and nitrite in water samples at low concentrations has been the focus of research [11].So far, many methods have been used to detect nitrate and nitrite, such as spectrophotometry [12][13][14], chemiluminescence [15,16], chromatography [17], fluorescence [18,19] and electrochemical methods [20][21][22]. Among them, the electrochemical method is one of the most commonly used detection methods because of its advantages of being low cost, fast, direct and high efficiency [23].…”
mentioning
confidence: 99%
“…The results can be processed with a microcontroller and transmitted to a monitor. Wang et al recently reported a comprehensive design of a hardware circuit for an optoelectronic sensor [41].…”
Section: Nitrite Sensing With Oled-opd Matrixmentioning
confidence: 99%
“…The first time the term paired emitter detector diode (PEDD) was used dates back to 1993 [ 33 ]. Since then, this methodology of paring a diode and photodiode has been successfully used for determining water quality parameters (nitrate, nitrogen [ 34 , 35 ], turbidity [ 36 ], phosphate [ 37 ], phosphorous [ 38 ], paraquat and diquat [ 39 ], fluoxetine and citalopram [ 40 ], and chromium [ 41 ]). Use of novel signal processing algorithms that can replace some hardware leads to better instrument performance at a lower cost.…”
Section: Introductionmentioning
confidence: 99%